Improving the outcome of acute stroke management - Hennerici, Michael G. (British journal of hospital medicine, 1999)
Recent research into stroke mechanisms suggests that it may be possible to reduce mortality and improve functional outcome in stroke patients, provided clinicians act quickly and appropriately. In this article, standards for optimal stroke management with new therapeutic strategies aiming to restore cerebral blood flow and to protect brain neurons will be discussed.